2008
DOI: 10.1038/ng.200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants near TNFAIP3 on 6q23 are associated with systemic lupus erythematosus

Abstract: SLE is an autoimmune disease influenced by genetic and environmental components. We performed a genome-wide association scan (GWAS) and observed novel association evidence with a variant inTNFAIP3(rs5029939, P = 2.89×10−12, OR = 2.29). We also found evidence of two independent signals of association to SLE risk, including one described in Rheumatoid Arthritis. These results establish that genetic variation inTNFAIP3contributes to differential risk for SLE and RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
406
2
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(418 citation statements)
references
References 12 publications
7
406
2
3
Order By: Relevance
“…More recently, this gene region has also been associated with SLE in two independent studies. 21,22 In Musone et al 22 three independent associations conferring risk were associated with SLE, including the two SNPs previously associated with RA. However, Graham et al 21 found two independent associations, one of which was previously associated with RA.…”
Section: Stat3mentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, this gene region has also been associated with SLE in two independent studies. 21,22 In Musone et al 22 three independent associations conferring risk were associated with SLE, including the two SNPs previously associated with RA. However, Graham et al 21 found two independent associations, one of which was previously associated with RA.…”
Section: Stat3mentioning
confidence: 98%
“…21,22 In Musone et al 22 three independent associations conferring risk were associated with SLE, including the two SNPs previously associated with RA. However, Graham et al 21 found two independent associations, one of which was previously associated with RA. Further analyses of the region will be required to establish if the associations in all three diseases are due to the same or different variant(s).…”
Section: Stat3mentioning
confidence: 98%
See 1 more Smart Citation
“…4,5 More recently, the advent of genome-wide association scans has allowed the identification of several non-MHC susceptibility genes, including IL12B, IL23R, RNF114, TNFAIP3, TNIP1, IL4/IL13 and LCE3B/3C [6][7][8][9][10][11] Of these, IL12B and IL23R harbour variants that also confer susceptibility to Crohn's disease (CD) 12 and ankylosing spondylitis. 13 Similarly, TNFAIP3 alleles have been associated with rheumatoid arthritis, 14 systemic lupus erythematosus 15 and type I diabetes. 16 Similar instances of genes conferring susceptibility to multiple conditions (for example, PTPN2, IL2RA and IL2) have emerged from other genome-wide association scans, 17,18 highlighting unexpected connections between clinically distinct disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This includes TNFAIP3, where it appears that at least one component of the RA risk is different from the SLE risk haplotype. [17][18][19] The shared risk factors appear to have unique overlaps between different autoimmune diseases. For example, the PTPN22 Arg620Trp that is sheared between several autoimmune diseases including T1DM and RA has been shown not to be a risk factor in MS, whereas in the present studies CD226 and CLEC16A variations are shared risk factors between MS and T1DM.…”
mentioning
confidence: 99%